Shooting food environments: Participatory video-making to support co-analysis and co-design of community action plans for improving adolescents’ food environments - Even, Brice; Thai, Hang Thi Minh; Nabuuma, Deborah; Mai, Truong Tuyet; Phuong, Ngo Thi Ha (2024)
This poster gives an overview of a participatory video-making process to support co-analysis and co-design of community action plans for improving adolescents’ food environments